Sensing viral RNAs by Dicer/RIG-I like ATPases across species - Paro, Simona (Curr Opin Immunol, 2015)
Induction of antiviral immunity in vertebrates and invertebrates relies on members of the RIG-I-like receptor and Dicer families, respectively. Although these proteins have different size and domain composition, members of both families share a conserved DECH-box helicase domain. This helicase, also known as a duplex RNA activated ATPase, or DRA domain, plays an important role in viral RNA sensing. Crystallographic and electron microscopy studies of the RIG-I and Dicer DRA domains indicate a common structure and that similar conformational changes are induced by dsRNA binding. Genetic and biochemical studies on the function and regulation of DRAs reveal similarities, but also some differences, between viral RNA sensing mechanisms in nematodes, flies and mammals.